ChatGPT in education: benefits and challenges of ChatGPT for mathematics and science teaching practices: International Journal of Mathematical Education in Science and Technology: Vol 0, No 0 (International Journal of Mathematical Education in Science and Technology, 2024)
This study investigates the utilisation and perceptions of artificial intelligence (AI) applications among mathematics and science teachers in enhancing students’ learning experience in mathematics classrooms. One prominent AI application this research seeks to explore, given its recent rise in popularity and usage, is ChatGPT. The study aims to explore the frequency and purpose of ChatGPT usage, its potential for student engagement, and its implementation’s perceived effectiveness, benefits, and challenges. A sample of 109 respondents was surveyed to gather insights into the usage patterns and perceptions of ChatGPT. The findings shed light on how teachers utilise ChatGPT, including generating examples, assessing difficulty, providing explanations, supporting problem-solving, and test preparation. Additionally, the study reveals that ChatGPT shows promise in enhancing student engagement and understanding. However, respondents highlighted challenges such as accuracy, connectivity, and language limitations. These findings contribute to our understanding of the role of AI technologies, specifically ChatGPT, in mathematics and science educational settings and provide valuable insights for the effective integration of AI in teaching and learning practices in various course contents and topics.
Keywords: AI: ChatGPT; Educational Area: Quality Teaching/Learning Materials; Educational Area: Teach; Evidence: Self-reported Teacher Behaviour/ Attitude; Location: Asia; Research Design: Qualitative Exploratory; Research Method: Qualitative; Source: Closed Source